Principle of Good Faith in Confidentiality Agreements of Trade Secret Information - Sudjana Sudjana (Faculty of Law, Maranatha Christian University, 2022)
This study aims to determine the category of agreement on confidentiality of Trade Secret Information in the perspective of contract law, Good Faith Criteria, and Legal Consequences for Disclosure of Trade Secrets in Confidentiality Agreement. Study results: (1). The category of confidentiality agreement based on its arrangement includes an anonymous agreement (not regulated in the Civil Code); according to the method of preparation including standard agreements (determined unilaterally by the owner of the Trade Secret) based on the principle of freedom of contract; is a formal agreement, namely the confidentiality agreement occurs not only in an agreement but also stated in a deed (under the hand); and in written form, namely Confidentiality Agreement; (2). The criteria for good faith based on the doctrine of subjective good faith and objective good faith are not disclosing Trade Secrets but Law no. 30 of 2000 does not explicitly regulate so that the criteria for good faith relate to the obligation to keep confidential referring to Article 1338 paragraph (3) of the Civil Code and doctrine or expert opinion. The legal consequences of disclosing a Trade Secret give rise to the right of the owner of the Trade Secret to take legal action, both litigation and non-litigation.